Verification of a real-time interactive transient simulator for Dalat Nuclear Research Reactor - Long, Cao Thanh; Tuan, Truong Hoang; Phuong, Huynh Dong; Khang, Nguyen Hoang Nhat; Dung, Ho Manh (Nuclear Science and Technology, 2020)
A PC-based real-time interactive transient simulator of Dalat Nuclear Research Reactor (DNRR), namely DalatSim, based on the best-estimate thermal-hydraulic code RELAP5/MOD3.3 has been currently building at Center for Nuclear Technologies (CNT). This paper presents the study on developing the physics core, control module, and human-machine interface (HMI) of DalatSim. The nodalization of DNRR used for DalatSim was based on the reported numerical model in the Safety Analysis Report (SAR) in 2012. DalatSim can simulate operational procedures and several hypothetical transient accidents of DNRR. A curve of real operational power of DNRR was used to compare with calculation power results from DalatSim to verify its capability. The verification results are presented and discussed.